Hamlet Goes Legit : Archaeology, Archive and Transformative Adaptation in Sons of Anarchy (FX 2008-2014) - Huertas-Martín , Víctor (International Journal of English Studies, 2022)
Using Shakespeare’s criticism and archival theory as lenses, this article enlarges understandings of the interconnections between a complex television series and Shakespeare. Forming a Shakespearean archive, Sons of Anarchy (SOA), based on Hamlet and other plays by Shakespeare, is packed with Shakespearean allusions, rather than citations, whose impact in the overall work is yet to be explored. Shakespearean formations, identifiable in the series’ para-texts, episodes, and transmedia materials, add political weight to SOA. This intertextuality invites us to regard Shakespeare’s influence in complex television as transformative.